Etude de la réponse immunitaire chez l'huître Crassostrea gigas : caractérisation et fonctions de protéines de reconnaissance aux LPS et d'effecteurs antimicrobiens - Gonzalez, Marcelo (Université Montpellier II, 2005)
Research on the immune response of oysters is motivated by the problems of infectious diseases potentially found in the farms. Over the course of the last few years, the development of genomic approaches has allowed us to make headway on characterising genes involved in the cup oyster's (Crassostrea gigas) innate immunity, particularly thanks to various programmes for analysing transcriptome, of type EST (Express Sequence Tag) and subtractive banks. Within the context of this work, over the course of which we have used the data from genomic research and we have also developed biochemical approaches, we were particularly interested in studying the proteins involved in reconnaissance reactions to LPS as well as to antimicrobial effectors. In an earlier part, we isolated, from the plasma, two proteins showing binding activities with the LPS of Gram-negative bacteria. We were able to identify the first isolated protein as being a Superoxide Dismutase of the extracellular type produced by haemocytes (Cg-EcSOD). Our results suggest that Cg-EcSOD has, in addition to its SOD activity, original LPS binding properties and could bind itself to haemocytes via a β integrin. The second protein, Cg-LBP (Lipopolysaccharide-Binding protein), isolated from the oyster's plasma, does not have any homology with the proteins from the databases and shows strong affinities for LPS. As far as the antimicrobial effectors are concerned, we characterised a gene coding a protein of type Bactericidal/Permeability Increasing protein, Cg-BPI, which is expressed in haemocytes and the epithelia as well as an antimicrobial peptide of type defensin (Cg-Def) from the oyster's mantle. Two other sequences of defensins (Cg-Defh) isolated from haemocytes were characterised. Functional studies of recombinant proteins show that Cg-BPI displays LPS binding properties as well as a permeabilisation of E. coli's external membrane. It is the first protein of type BPI characterised in an invertebrate. Defensin Cg-Def displays a spectrum of antimicrobial ...